COMPARISON OF STONE FREE RATE OF STAGHORN STONE, RENAL PELVIC STONE, AND INFERIOR CALYX STONE FOLLOWING PCNL - Tirtayasa, Pande Made Wisnu; Birowo, Ponco; Rasyid, Nur (Indonesian Journal of Urology, 2016)
Objective: To compare the stone free rates on patients with staghorn, renal pelvic, and inferior calyx stones with stone burden < 20 mm, 21-30 mm, and > 30 mm following percutaneous nephrolithotomy (PCNL) in Cipto Mangunkusumo General Hospital Jakarta. Material & methods: The data were collected retrospectively from PCNL medical records in Cipto Mangunkusumo General Hospital Jakarta between January 2000 and March 2011. Six hundred and twenty-three patients with 651 kidney stones underwent PCNL. The inclusion criteria were staghorn stones, renal pelvic stone, and inferior calyx stone. All cases outside these three criteria and incomplete data were excluded. Stone free status was defined as no residual fragment on radiography or ultrasonography. Results: As many as 364 kidney stones from 344 patients were included, with 47.8% cases of staghorn stones, 31.9% cases of renal pelvic stones, and 20.3% cases of inferior calyx stones. Overall, 273 (75%) cases were defined as stone free. In group < 20 mm, 4 staghorn stones (100%), 18 renal pelvic stones (81.8%), and 34 inferior calyx stones (94.4%) were cleared (p = 0.811). In group 21-30 mm, 20 staghorn stones (95.2%), 52 renal pelvic stones (91.2%), and 26 inferior calyx stones (92.9%) were cleared (p = 1.000). In group > 30 mm, 83 staghorn stones (55.7%), 28 renal pelvic stones (75.7%), and 8 inferior calyx stones (80%) were cleared (p = 0.037). Conclusion: PCNL is an important tool for treating various kinds and sizes of kidney stones with high stone free rate.